Genetic divergence of cassava genotypes from Petrolina - André Luiz Pinto dos Santos; Guilherme Rocha Moreira; Diego Alves Gomes; Marcela Portela Santos de Figueiredo; Maria Lindomárcia Leonardo da Costa; Moacyr Cunha Filho; Eloísa de Oliveira Simões Saliba; Cristiane Rocha Albuquerque (Acta Scientiarum. Animal Sciences, 2023)
This study aimed to evaluate cassava genotypes to identify the ones with the best nutritional values for ruminant diets. Nine genotypes were used: Amansa Burro (BGM 549), Aramaris (BGM 116), Brasília, Cambadinha (BRS Guaíra), Curvelinha, Engana Ladrão (BGM 1269), Trouxinha (BGM 1468), BRS Gema de Ovo, and BRS Dourada. A completely randomized block experimental design with nine treatments (genotypes) and three blocks (replicates) were employed. The roots were analyzed for dry matter production (DMP) in tonnes per hectare, crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), starch, and in vitro dry matter digestibility (IVDMD). The multivariate analysis was carried out using Ward’s hierarchical agglomerative clustering based on Mahalanobis distance. The groups formed were evaluated by Scott-Knott test. The group formed by genotype Engana Ladrão was chosen as the best one for having the highest DMP t ha-1 and IVDMD values and the lowest NDF and ADF contents.